Radioactivity distribution in the blood and urine of patients receiving systemic therapy with a 177Lu radiopharmaceutical and local (intra-articular) therapy with a 188Re radiopharmaceutical - E. D. Stepchenkova; V. K. Tishchenko; O. P. Vlasova; V. M. Petriev; N. S. Legkodimova; V. V. Krylov; A. V. Fedorova; E. A. Kuzenkova; A. A. Ostroukhoff; P. V. Shegai (Регуляторные исследования и экспертиза лекарственных средств, 2022)
Pharmacokinetic parameters are important for calculating the absorbed dose; they also provide an indirect measure of the in vivo stability of a radiopharmaceutical. The aim of the study was to determine the excretion rate of the activity of 177Lu-DOTA-PSMA-617 and MCA 5–10 microns, 188Re, from the blood and urine of patients undergoing systemic and local radiotherapy in clinical trials. Materials and methods: the study involved radiometry of blood and urine samples of 12 male patients with metastatic prostate cancer and 20 patients of both sexes with chronic synovitis, selected after radiotherapy with the experimental radiopharmaceuticals 177Lu-DOTA-PSMA-617 and MCA 5–10 microns, 188Re, respectively. The activity of the samples was measured using a dose calibrator and a gamma counter. Results: the activity of 177Lu in the blood of patients was 36.0–89.3%, 10.4–55.7%, 14.6–32.8%, 10.6–35.7%, and 7.3–25.1% at 5 minutes and at 1, 3, 6 and 8 hours after the administration of 177Lu-DOTA-PSMA-617, respectively. The 48-hour urine excretion varied within 34.4–88.8% for 177Lu-DOTA-PSMA-617 and within 0.15–2.91% for MCA 5–10 microns, 188Re. Conclusions: the maximum values of 177Lu-DOTA-PSMA-617 activity in the blood 8 hours after administration (9.6–25.1%) corresponded to the maximum injected activity of the radiopharmaceutical product. The low rate of 188Re urinary excretion after intra-articular administration of MCA 5–10 microns, 188Re, is an indirect indication of the quality of the radiopharmaceutical. The obtained pharmacokinetic parameters show high in vivo stability of the 177Lu and 188Re medicinal products. The results obtained will be used to calculate absorbed doses in patients.